Comparison of Body Mass Index and Bioelectric Impedance Analysis Methods in the Evaluation of Body Composition and Obesity in Women - Sırıken, Fatih; Ertekin, Ersen; Ünsal, Cengiz; Ertekin, Arif Aktuğ; Öztürk, Hakan; Rodriguez, Anna Beatriz; Pekcan, Ayla Gülden (Erkan Mor, 2022)
Objective: Body mass index (BMI) is often used to diagnose obesity, although it has the disadvantage of not being able to reveal body fat content. Our study aimed (1) to evaluate the obesity status using BMI and body fat percentage (BFBIA%) determined by bioelectric impedance analysis (BIA) method among women aged 20-60 years who were admitted the outpatient nutrition clinic, and (2) to evaluate the relationship between BMI and BFBIA%. Method: This study enrolled 100 women aged 20-60 years. It was a descriptive study. The study data and the BFBIA% values were obtained from outpatient BMI data recorded between October 2020 and November 2020. BMI was calculated using body weight (kg) and body height (m2). The prevalence of obesity was determined using BMI and BFBIA%. Statistical analyses were performed using the Pearson’s correlation test and One-Way analysis of variance. Results: Prevalence of obesity, based on BMI and BFBIA%, was 53% and 46%, respectively and no significant difference was determined (p=0.322). Subjects determined to be obese based on the BMI had a mean BFBIA% of 40±18%. The subjects determined to be obese, overweight and normal based on the BMI had a mean BFBIA% of 40.4±5.3, 34.4±4.1, and 23.2±6.2, respectively (p<0.001). Conclusion: The obesity rates determined by BMI and BFBIA% were similar. Since both BMI and BFBIA% have different disadvantages, their combined use may yield better results in obesity screening in outpatients.

Amaç: Obezite tanısında sıklıkla beden kütle indeksi (BKİ) kullanılmakla birlikte, vücut yağ düzeyini ortaya koymaması dezavantajlı noktasıdır. Bu çalışmanın amaçları diyet polikliniğine başvuran, (1) 20-60 yaş grubu kadın bireylerde, BKİ ve biyoelektrik impedans analiz yöntemi (BİA) ile doğrudan saptanan vücut yağ yüzdesini (VYBİA%) kullanarak obezite durumunu ve (2) BKİ ve VYBİA% arasındaki ilişkiyi değerlendirmektir. Yöntem: Çalışma 20-60 yaş arası 100 kadın bireyle yürütülmüştür. Bu araştırma tanımlayıcı tiptedir. Araştırma verileri ve vücut yağ yüzdesi (% BFBİA) değerleri, poliklinik BİA kayıtlarından Ekim-Kasım 2020 arasında elde edilmiştir. Vücut ağırlığı ve boy uzunluğu ölçümleri kullanılarak BKİ hesaplanmıştır. Bireylerde obezite görülme sıklığı BKİ ve vücut yağ yüzdesi (VYBİA%) kullanılarak belirlenmiştir. İstatistik olarak Pearson korelasyon testi ve tek-yönlü varyans analizi kullanılmıştır. Bulgular: BKİ’ye göre kadınların %53’ü, BİA ile elde edilen vücut yağ yüzdesine göre %46’sı obez bulunmuştur. BKİ ve vücut yağ yüzdesi kullanılarak saptanan obezite arasında anlamlı bir fark bulunmamıştır (p=0,322). BİA’ya göre obez bireylerin ortalama vücut yağ yüzdesi (VYBİA%) %40±18 olarak saptanmıştır. BİA yöntemi kullanılarak BKİ’ye göre şişman, hafif şişman ve normal vücut ağırlığındaki kadınların vücut yağ yüzdeleri ise sırasıyla %40,4±5,30, %34,4±4,1, ve %23,2±6,2 olarak belirlenmiştir (p<0,001). Sonuç: BKİ ve VYBİA% birbiriyle pozitif olarak ilişkilidir. Vücut yağ yüzdesinin eşlik ettiği BKİ, kadın bireylerde şişmanlığın daha iyi bir tanımlanmasını sağlayabilir.
Kadınlarda Vücut Kompozisyonu ve Obezitenin Değerlendirilmesinde Beden Kütle İndeksi ve Biyoelektrik İmpedans Analiz Yöntemlerinin Karşılaştırılması
Keywords: beden; kütle; obezite; vücut; yağ